Manajemen Kurikulum Pesantren dalam Meningkatkan Kemampuan Bahasa Arab Siswa Tingkat Madrasah Aliyah - Andaru Bahy, Moh. Buny; Wahidmurni; Hadi, Nur (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2024)
Knowledge of curriculum management is crucial in determining the direction of education. Managing the pesantren curriculum is one of the key foundations for improving students' Arabic language skills. Therefore, research on pesantren-based curriculum management should be conducted. This study aims to understand the general concepts, characteristics, and scope of curriculum management in general and pesantren-based curriculum management. This research employs a qualitative descriptive method with field research. The primary data for this study was obtained from Madrasah Aliyah Attanwir Bojonegoro, while secondary data was sourced from relevant literature. The purpose of this research is to identify the concepts, characteristics, and implementation of pesantren-based curriculum management in enhancing students' Arabic language skills. After conducting an in-depth analysis, this study found that the concept of pesantren curriculum management still adheres to the basic principles of general curriculum management, but there are differences in the objectives, which focus more on the curriculum of Arabic language learning, and Islamic studies. In its implementation, the pesantren curriculum management at Madrasah Aliyah Attanwir Bojonegoro adopts a semi-modern pesantren curriculum, thus positively impacting students' Arabic language learning. Moreover, the semi-modern pesantren curriculum also enhances students' Arabic language skills both theoretically and practically.